Collaborative Outcome Mapping - and Dart, J.; Roberts, M. (2014)
Collaborative Outcomes Reporting (COR) is a participatory approach to impact evaluation based around a performance story that presents evidence of how a program has contributed to outcomes and impacts, that is then reviewed by both technical experts and program stakeholders, which may include community members. Collaborative Outcomes Reporting (COR) is a participatory approach to impact evaluation based around a performance story that presents evidence of how a program has contributed to outcomes and impacts, that is then reviewed by both technical experts and program stakeholders, which may include community members. Developed by Jess Dart, COR combines contribution analysis andMultiple Lines and Levels of Evidence (MLLE), mapping existing data and additional data against the program logic to produce a performance story. Performance story reports are essentially a short report about how a program contributed to outcomes. Although they may vary in content and format, most are short, mention program context and aims, relate to a plausible results chain, and are backed by empirical evidence (Dart and Mayne, 2005). The aim is to tell the ‘story’ of a program’s performance using multiple-lines of evidence. COR adds processes of review by an expert panel and stakeholders, sometimes including community members, to check for the credibility of the evidence about what impacts have occurred and the extent to which these can be credibly attributed to the intervention. It is these components of expert panel review (outcomes panel) and a collaborative approach to developing outcomes (through summit workshops) that differentiate COR from other approaches to outcome and impact evaluation.